2017
DOI: 10.17140/pcsoj-3-121
|View full text |Cite
|
Sign up to set email alerts
|

A Psychophysical Approach to Test: “The Bignetti Model”

Abstract: The cognitive "Bignetti Model" (TBM) thoroughly discussed elsewhere, shares a strong analogy with "Learning Through Experience" (LTE) and Bayesian Learning Process (BLP). Here, TBM's theory is challenged by means of a psychophysical press/no-press decision task (DT). Participants must press a computer key in response to sweet food image (SWEET) or refrain from doing it with a salted food image (SALTED) (24 trials each, mixed at random in a 48-trial DT). Reaction times (RT) plotted as a function of trials decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…A fifth example regards the data obtained through a series of cognitive "press/ no-press" psychophysical test (Bignetti et al, 2016;Aimi et al, 2018). In line with the third example reported above, we have demonstrated the reaction of young subjects to repetitive trials were shortening so much until they become compatible with automatic reactions; they became so short that CM could not even recognize the test's items.…”
Section: The 5 Th Examplesupporting
confidence: 83%
“…A fifth example regards the data obtained through a series of cognitive "press/ no-press" psychophysical test (Bignetti et al, 2016;Aimi et al, 2018). In line with the third example reported above, we have demonstrated the reaction of young subjects to repetitive trials were shortening so much until they become compatible with automatic reactions; they became so short that CM could not even recognize the test's items.…”
Section: The 5 Th Examplesupporting
confidence: 83%
“…So, the question is whether "to choose" implies a conditioned or conditional act; the theoretical and practical implications of this answer on human cognition are overwhelming. Therefore, the possibility that individual believe in FW might play a fundamental role in cognition, has been deeply investigated by the author and coworkers (Bignetti, 1994(Bignetti, , 2001(Bignetti, , 2003(Bignetti, , 2004(Bignetti, , 2010, 2017Bignetti et al, 2016;Aimi et al, 2018). At first, data demonstrated that brain is a probabilistic-deterministic machine (Koch, 1999;Bignetti, 2003); as an example, see: "Galton Board" in which the falling down balls randomly bounce either left or right, with the same probability.…”
Section: Free-willmentioning
confidence: 99%
“…Unlike the numerous theories and models about the mechanism of human cognition till now present in the literature, TBM is really the unique one that reconverts FW-illusion into an essential ingredient on which cognitive processes underlie. To validate this hypothesis, recently, Bignetti et al [19][20] carried out press/no-press psychophysical experiments by using salted and sweet foods images (respectively "press" and "no-press" cues) that were projected onto a computer screen. Upon cue recognition, subjects had to decide whether to press or not, as fastest as possible.…”
Section: Motivations and Rewards In Tbmmentioning
confidence: 99%
“…Recently, Bignetti et al have carried out some experiments of classic psychophysics to test TBM; the data could be easily interpolated by rational curves derived from a mathematical model that is compatible with TBM. [19][20] The first psychophysical experiments are not enough to consider TBM's theory validated. A more appropriate analytical method (e.g.…”
Section: Introductionmentioning
confidence: 99%